Peri-urban Mountain Trails of Cusco, Peru: A Multi-Criteria Approach to Assess their Ecotourism Suitability - Bellota, Edwin (2026)
Andean cities are often located at the bottom of valleys surrounded by mountains of varying altitudes. With appropriate management, these peri-urban areas offer an opportunity to reconnect urban populations with nature and to harness the benefits associated with green spaces, with ecotourism representing a potential pathway for their sustainable preservation. To assess the ecotourism suitability of these spaces, and considering hiking as the primary mode of interaction with nature, a multi-criteria decision analysis (MCDA) framework was developed to prioritize mountain trails. The study was conducted in the peri-urban surroundings of the city of Cusco (Peru, 3,300 m.  a. s. l.), evaluating approximately 220 km of hiking routes. Ten routes were identified and characterized using five criteria: plant diversity, presence of archaeological sites, landscape diversity, hiking difficulty, and local population attitude toward the implementation of ecotourism trails. Overall, the analyzed trails contain 384 plant species, a wide range of archaeological sites linked to Cusco’s historical role as the capital of the Inca Empire, three types of landscapes (life zones), and hiking difficulty levels ranging from moderate to difficult. Results indicate that local community willingness to support ecotourism initiatives decreases with proximity to the urban center and with inclusion within culturally protected areas, such as the Saqsaywaman Archaeological Park. The MCDA application demonstrates that without the support of landowning communities, the viability of ecotourism as a conservation strategy is limited, highlighting local population attitude as a critical factor in decision-making processes.